Kualitas Mobile Banking Terhadap Kepuasan Nasabah Bank BRI (Studi Pada Pengguna BRI Mobile di Kota Depok) - Ratnawaty Marginingsih (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2020)
Abstract  - The utilization of technology in the banking industry such as mobile banking or often referred to as m-banking provides convenience in financial transactions. There are services on mobile banking, covering payments transfer, history, and others.The use of mobile banking services in cell phones allow that customers can more easily to run their banking activities indefinitely space and time.This study aims to determine the effect of the quality of mobile banking services on BRI Bank customer satisfaction in the city of Depok. A total of 100 respondents were surveyed online using the convenience sampling method. The form of research used is descriptive research with a quantitative approach. The data is processed using multiple linear regression analysis. The results of this study are obtained partially and simultaneously the quality of service using the variables reliability and responsiveness, assurance and security, convenience in banking, mobile banking efficiency and easy to use on customer satisfaction to obtain positive and significant results. This shows that good service is one of the keys to the success of an organization Keywords : Service Quality, Customer Satisfaction, Mobile Banking